The influence of temporary differences between accounting and tax revenues, proprietary costs and liquidity on profit growth - NURAMALIA HASANAH; RIDA PRIHATNI; AYUMASTUTININGSIH AYUMASTUTININGSIH (Jurnal Ilmiah Wahana Akuntansi, 2017)
This study aimed to examine the influence of temporary differences between accounting profit and tax, proprietary costs, and Liquidity toward earnings growth of the companies listed in Indonesia Stock Exchange (IDX) 2011-2012. The factors examined in this study are temporary differences between accounting profit and tax, proprietary costs, and liquidity as an independent variable, while earnings growth has the dependent variable. This study used a descriptive quantitative method using secondary data and the number of samples collected was thirty- eight (38) that have met the criteria the researchers used purposive sampling. From the data that has been collected and then processed and analyzed using multiple regression analysis with a significance level of 0.05. This research proves temporary differences between accounting profit and tax has no significant influence on earnings growth, proprietary cost has no significant influence on earnings growth, and liquidity has negatively significant influence earnings growth. Temporary differences between accounting profit and tax, proprietary costs, and liquidity together or simultaneously significant influence toward the earnings growth.